2020
DOI: 10.2147/idr.s242304
|View full text |Cite
|
Sign up to set email alerts
|

<p>Palmatine Is a Plasmid-Mediated Quinolone Resistance (PMQR) Inhibitor That Restores the Activity of Ciprofloxacin Against QnrS and AAC(6ʹ)-Ib-cr-Producing <em>Escherichia coli</em></p>

Abstract: The emergence of plasmid-mediated quinolone resistance (PMQR) is a global challenge in the treatment of clinical disease in both humans and animals and is exacerbated by the presence of different PMQR genes existing in the same bacterial strain. Here, we discovered that a natural isoquinoline alkaloid palmatine extracted from traditional Chinese medicinal plants effectively inhibited the activity of PMQR proteins QnrS and AAC(6′)-Ib-cr. Methods: In total 120 clinical ciprofloxacin-resistant Escherichia coli (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…and in other Enterobacteriaceae with increasing prevalence (Pribul et al., 2016 ). PMQR determinants generally generate only low‐level resistance, but nonetheless can complement the mechanisms of chromosomal resistance to reach clinical resistance levels (Wang et al., 2020 ). The recent discovery of PMQR could result in horizontal transfer of fluoroquinolone resistance between strains (Hopkins et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…and in other Enterobacteriaceae with increasing prevalence (Pribul et al., 2016 ). PMQR determinants generally generate only low‐level resistance, but nonetheless can complement the mechanisms of chromosomal resistance to reach clinical resistance levels (Wang et al., 2020 ). The recent discovery of PMQR could result in horizontal transfer of fluoroquinolone resistance between strains (Hopkins et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structure of UA (compound CID: 1175) and 5-methyltetrahydrofolic acid (compound CID: 135415868) was obtained from the PubChem Compound database. Chem3D 16.0 software was used to calculate the conformation optimized before docking . LigPlot + v.2.2 was employed to investigate the docking model complexes.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the roles of palmatine as anti-virulence agents against bacterial pathogens have been clarified. Wang et al found that palmatine could inhibit the activity of plasmid-mediated quinolone resistance (PMQR) proteins QnrS and AAC(6′)-lb-cr, and could restore PMQR-mediated ciprofloxacin resistance of Escherichia coli [ 49 ]. Moreover, palmatine has been identified as a Sortase A inhibitor by binding to the catalytic center of the enzyme [ 50 ].…”
Section: Discussionmentioning
confidence: 99%